To form a quadratic equation, let α and β be the two roots.
Let us assume that the required equation be ax22 + bx + c = 0 (a ≠ 0).
According to the problem, roots of this equation are α and β.
Therefore,
α + β = - baba and αβ = caca.
Now, ax22 + bx + c = 0
⇒ x22 + babax + caca = 0 (Since, a ≠ 0)
⇒ x22 - (α + β)x + αβ = 0, [Since, α + β = -baba and αβ = caca]
⇒ x22 - (sum of the roots)x + product of the roots = 0
⇒ x22 - Sx + P = 0, where S = sum of the roots and P = product of the roots ............... (i)
Formula (i) is used for the formation of a quadratic equation when its roots are given.
Given the roots: (-1+-i)
where; i=sqrt(-1)
Thus, the answer is (2x)
You can also do checking to verify if x^2+2x+2 will have roots equal to (-1+-i)